Penguatan Citra Brand Kosmetik Lokal dalam Menjangkau Konsumen Muda Secara Digital - Larasati, Ni Luh Sekar Ayu Dewi; Handayani, Wiwik (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the ways in which local brands strengthen their image and reach young consumers by making maximum use of digital media. The background stems from the low awareness and knowledge of this group about local brands, as many of these products are rarely highlighted due to minimal online exposure. In a highly competitive digital environment, an active presence on social platforms is now an essential requirement to attract the attention of the younger generation who are more visually and emotionally connected. This research is qualitative, using case studies, and collected data through online activity observations, in-depth interviews with internal staff, and analysis of social media content documents. The findings show that the strategies used include producing attractive visual content, collaborating with influencers who match the audience's hinton, and sending messages that are educational, authentic, and in line with the lifestyle of young people. In addition to increasing brand visibility, this approach also builds emotional closeness, improves consumer views, and encourages loyalty to local goods. In other words, the positive image of local cosmetic brands is not only determined by product quality, but also by the success of digital communication strategies that are in line with the media habits and tastes of today's young generation.